The connection between subjective wellbeing and pro-environmental behaviour: Individual and cross-national characteristics in a seven-country study. Issue 133 (July 2022) - Capstick, Stuart; Nash, Nicholas; Whitmarsh, Lorraine; Poortinga, Wouter; Haggar, Paul; Brügger, Adrian
Abstract: A positive and reciprocal relationship between subjective wellbeing and pro-environmental behaviour (PEB) has been observed across a range of countries worldwide. There is good reason however to think that the nature of the PEB-wellbeing link might vary between individuals and cross-culturally. We use data obtained in Brazil, China, Denmark, India, Poland, South Africa and the UK (total n = 6969) to test a series of hypotheses using pre-registered regression models. First, we assess the relationship between PEB and wellbeing across countries, and test the 'privilege' hypothesis that this varies according to personal income and a country's level of development. Second, we consider the role of individual values and motivations in relation to PEB and wellbeing. To this end, we test the 'enhancement' hypothesis, in which the PEB-wellbeing link is strengthened by people holding particular values and motivations. Third, we consider the role of cultural differences for the nature of the PEB-wellbeing link. We test the 'social green' hypothesis that public sphere behaviours (e.g. addressing environmental issues with other people) are more closely linked to wellbeing than are private sphere behaviours (e.g. product purchasing) in collectivistic cultures; in tandem, we assess whether private sphere behaviours are more closely linked to wellbeing in individualistic cultures. We obtain strong evidence for a PEB-wellbeing link across nations. There is partial evidence across countries to support the 'social green' hypothesis, but little evidence for the 'privilege' or 'enhancement' hypotheses. We discuss the implications of our findings for understanding the relationship between PEB and wellbeing, and consider how its promotion might feature in environmental and public health policy. Highlights: We investigate the relationship between pro-environmental behaviour (PEB) and subjective wellbeing across seven countries. Cross-cultural evidence is obtained for a PEB-wellbeing link. This was most pronounced in India and China. We obtain no evidence that people's income, or values and motivations, moderate the relationship between PEB and wellbeing. Socially-oriented PEB is more strongly linked to wellbeing than individual-level action in collectivistic cultures. Environmental policy should be alert to the potential for enhancing personal wellbeing as a co-benefit of carrying out PEB.